Diagnostic CT cystography with diluted gadolinium-based contrast: A viable alternative to an iodinated contrast-based cystogram - Brian Holmes; Sreeja Sanampudi; Lakshmi Ananthakrishnan (Urology Case Reports)
Patients with reported history of severe iodinated contrast reaction are not uncommon in daily practice. Iodinated contrast is most frequently administered intravenously (IV) for CT scans but is also used intraluminally during urologic procedures and postoperatively to assess for leaks. Providers often are unaware that patients with prior iodinated contrast allergy after IV administration are still at risk for a reaction during intraluminal administration. We present a case of a patient with history of iodinated severe contrast allergy, in which CT cystography using a gadolinium-based-contrast agent was safely performed as an alternative to iodinated-based-cystography to evaluate for a postoperative leak.